The Dispositions of Student-Teachers in Developing Competencies through Written Self-reflection Practice - Rahayu Apriliaswati; Iit Fitrianingrum (RIRAI Publisher, 2022)
This study aimed at investigating how student-teachers develop their competencies through written self-reflection. It is a case study of descriptive research that investigates how student teachers develop their dispositions through self-reflection practice in the classroom. The data were collected through written self-reflection made by the student-teachers. There were 40 English student-teachers at English Education Study Program were taken as the subject. Results show that written self-reflection has assessed English student-teachers ‘dispositions towards developing competencies. For Professional Competence, all English student teachers practice their language skills by doing the assignments given by lecturers regularly, seriously, collaboratively, and proudly. For Pedagogical Competence, all student teachers practice creative lesson plans, develop interesting teaching materials through peer teaching; whereas for Personality Competence all student teachers are aware of 18 indicators of personality and apply them in their daily activities by studying harder, respecting others, preparing for class, accepting to different opinions, being more patient and helpful. Similar to Personality Competence, English student teachers demonstrate positive dispositions towards social skills by doing real actions of 21 indicators of social skills such as greeting, speaking more politely, addressing lecturers/friends appropriately, engaging in a friendly dialogue in their daily activities. By written self-reflection, the student teachers have shown their performance of their dispositions and been aware of developing teacher competencies.